Digitalização das linguagens, transformações semióticas, sociais e educação midiática para o ensino básico - Botelho, Thaïs Helena Falcão (2024)
In the first part of the 21st century, there has been an exponential advance in digital media and media languages throughout the world. Brazil has stood out worldwide with its presence in these media. Despite this, a worrying trend of a lack of skills appeared internationally. Faced with a reality in which a series of solutions and relationships take place through the media, and a lack of media education for children can be as damaging as not teaching them how to read or write. The aim of this study was to verify, through the guiding documents of public policies in the country, such as the National Broadband Plan and the Textbook and Teaching Material Program, whether they contained guidelines for media education, such as learning for other languages, with semiotic approaches, especially digital ones. At the same time, in order to better understand the need to adopt digital media in education, some of the motivations for the creation of the Web and how some processes of digitization of media and their languages have taken place are pointed out. From this, it can be seen that for a language to be used universally, semiotic and standardization processes are necessary. This happened with written language, which made it possible for it to be adopted in large-scale . When it became ubiquitous, due to its multiplication in print, a series of pedagogical processes for literacy began. After the advent of computer technologies, similar procedures took place with digital languages. They were created through semiotic processes and standardization. As a result they have also become universal and consequently, pedagogical processes, such as media education are necessary for the personal promotion of citizens and a nation.Due to the lack of materials and methodologies for this learning, at the end of this thesis we present a pedagogical strategy for its learning